Topics in Local Anesthetics - Whizar-Lugo, Víctor M.; Hernández-Cortez, Enrique (IntechOpen, 2020)
The fascinating history of local anesthetics was born in the Andean Mountains with the use of Erythroxylum coca and has gradually evolved into a group of safe drugs in anesthesiology and pain medicine. Their mechanism of action on the cell membrane produces anesthesia, analgesia, and side effects that can be catastrophic. Other effects such as antimicrobial, anti-inflammatory, antineoplastic, and other therapeutic results have also been found and are still under investigation. Pharmacological advances in local anesthetics, the use of adjuvant drugs, and new regional anesthesia techniques have resulted in greater efficacy and safety for patients.Written by authors from around the world, this book examines selected topics on local anesthetics and their current use in clinical practice.